Pengembangan Bahan Ajar Berbasis Kearifan Lokal dengan Media Flipbook untuk Meningkatkan Literasi Budaya dan Kewargaan - Anengsih Anengsih; Heni Pujiastuti; Ratna Sari Dewi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to produce flipbooks as local wisdom-based teaching materials that can encourage cultural and civic literacy and strengthen character education among students. These teaching materials include information about Tangerang City, the Palang Pintu tradition, and the Lenggang Cisadane dance. The process of developing these teaching materials follows the ADDIE model. Data were collected through interviews, questionnaires, and tests, where the questionnaires included assessments from media experts, material experts, and student responses, while the tests consisted of Pre-test and Post-test. Data analysis was carried out using t-test and n-gain tests. The research sample involved 30 fourth-grade students at SDIT Tunas Harapan Ilahi, Tangerang City, Banten. The results of the study showed that the development of teaching materials carried out was classified as